Treatment agent that achieves shortened process for Anti-glare and Anti-fouling laminate treatment and improved durability, and coating method
The novel antiglare treatment agent composition and coating method address the challenges of hazardous chemicals, high costs, and inefficiencies in existing technologies by using a hydrolyzed condensate of tetraalkoxysilane compounds and organic solvents, resulting in a durable, efficient, and environmentally friendly antiglare coating with improved wear resistance.
Patent Information
- Application Number
- JP2024228742
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-07-26
AI Technical Summary
Existing antiglare treatment methods for glass substrates in image display devices face challenges such as the use of hazardous chemicals like hydrofluoric acid, high costs, and issues with uniformity on curved surfaces. Additionally, the high-temperature baking process required for conventional spray coating methods is inefficient for mass production and can lead to flaking and unevenness of the antiglare layer.
A novel antiglare treatment agent composition is developed, comprising a hydrolyzed condensate of a tetraalkoxysilane compound under a strong acid catalyst and an organic solvent, which is spray-coated and then baked to form a laminated coating. This method reduces the baking time and prevents the formation of unevenness due to staining, resulting in a durable antiglare coating with improved wear resistance.
The new method achieves a coating film with excellent durability and antiglare properties, reducing the environmental impact by avoiding hazardous chemicals and improving production efficiency through shorter processing times. The coating exhibits good haze, gloss, and water contact angle retention even after multiple wear cycles, demonstrating enhanced wear resistance and durability.
Smart Images

Figure 2025039591000001 
Figure 2025039591000002 
Figure 2025039591000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an antiglare treatment composition, a coating method for an antifouling treatment agent to be laminated thereon, and an antiglare and antifouling coating film. [Background technology]
[0002] In image display devices such as liquid crystal displays and organic electroluminescence displays, a phenomenon occurs in which visibility is reduced due to reflected images caused by light from indoor lighting devices such as fluorescent lights or external light such as sunlight. To prevent this, it is common practice to apply anti-glare treatment (AG treatment) or anti-reflection treatment (AR treatment) to glass substrates such as the cover glass of image display devices. The anti-glare treatment of these glass substrates is realized by forming unevenness on the surface by etching, sandblasting, coating or the like, thereby causing diffuse reflection of external light. Among these methods, the mainstream etching method uses hydrofluoric acid, which is highly corrosive and highly toxic to the human body, and therefore poses serious problems for the working environment and the global environment. There are also issues that need to be improved from the standpoint of cost and ensuring uniformity in curved display surfaces (Patent Documents 1 to 3).
[0003] Therefore, relatively simple coating methods have begun to be considered again as an alternative to the etching method. Among these, the method of spraying an anti-glare treatment composition allows easy control of film thickness and optical properties by changing the coating conditions, and can be performed using small-scale equipment. However, a high-temperature baking process is required to dry the solvent after spraying, and further reductions in processes are expected in order to use this method in mass production (Patent Documents 4-6).
[0004] On the other hand, for applications where the surface is touched by fingers, such as touch panels, an anti-soiling layer made of a fluorine-containing organic silicon compound may be laminated on top of the anti-glare treatment layer to prevent stains such as fingerprints and sebum from impairing visibility and aesthetics (AF treatment). Antifouling treatment forms a highly water- and oil-repellent film to prevent dirt from adhering, but this performance is easily degraded by repeatedly wiping off the dirt that has adhered to the surface. Therefore, there is a need for a method to improve the abrasion resistance and durability of the antifouling layer. To solve this problem, in order to increase the adhesion between the antiglare layer and the antifouling layer, a surface modification process such as glow discharge emission, plasma exposure, or washing with an alkaline solution may be performed on the antiglare treatment layer before the antifouling treatment agent is applied (Patent Documents 7-8). However, the effect is not sufficient considering the increased number of manufacturing steps, and further improvement is required. In addition, the antifouling agent exerts its effect by being evenly applied to the top surface of the previously formed AG layer. However, if any foreign matter adheres to the AG layer in the previous process, it can cause repellency problems and uneven coating. Therefore, it is necessary to strictly control the inclusion of foreign matter in the baking oven. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2012-521958 [Patent Document 2] Special Publication No. 2014-513029 [Patent Document 3] Special Publication No. 2014-523384 [Patent Document 4] JP 2018-198050 A [Patent Document 5] JP 2009-058640 A [Patent Document 6] JP 2017-106944 A [Patent Document 7] JP 2022-007992 A [Patent Document 8] Republished Patent 2019 / 189071 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention aims to solve the problems and issues in the prior art described above and to provide an antiglare (AG) treatment composition capable of imparting highly durable antiglare and antifouling properties to glass materials and the like in a short period of time, a method for applying the same, and a coating film obtained by applying the same. [Means for solving the problem]
[0007] As a result of intensive research into the above-mentioned issues and problems, the inventors have discovered that these can be overcome by spray-coating, under certain conditions, an AG treatment agent consisting of a hydrolysis condensation product of a tetraalkoxysilane compound under a strong acid catalyst, and an alcohol or glycol ether-based organic solvent, and then spray-coating a fluorine-containing antifouling treatment agent and baking the resulting coating, thereby completing the present invention. The present invention is characterized in the following points. 1. An anti-glare treatment composition comprising a hydrolysis condensation product of a tetraalkoxysilane compound in the presence of a strong acid catalyst, and an alcohol and / or a glycol ether organic solvent. 2. An anti-glare treatment composition comprising 5 to 50 parts by mass of a hydrolysis condensate of a tetraalkoxysilane compound per 100 parts by mass of the anti-glare treatment composition, and the organic solvent is one or more mixed solvents, and is present in an amount of 50 to 95 parts by mass per 100 parts by mass of the anti-glare treatment composition. 3. A method for forming a coating film having anti-glare and anti-fouling properties using the anti-glare treatment composition described in 1 or 2 above, characterized in that the anti-glare treatment composition is spray-coated onto the surface of an article to be coated to form an anti-glare treatment composition layer, and then a fluorine-containing anti-fouling treatment agent is spray-coated, followed by baking. 4. A method for forming a coating film having anti-glare and anti-soiling properties as described in 3 above, characterized in that an anti-soiling treatment agent is spray-coated on the anti-glare treatment composition layer while the heating residue measured after heating at 180°C for 1 hour is 74 to 95 parts by mass. 5. An antiglare and antifouling layer comprising an antiglare layer made of the antiglare treatment composition according to 1 or 2 above, and an antifouling layer made of a fluorine-containing antifouling treatment agent.
[0008] "Anti-glare treatment composition" The composition forming the antiglare treatment agent used in the present invention is as follows. The anti-glare treatment composition contains a hydrolysis condensate of a tetraalkoxysilane compound in the presence of a strong acid catalyst, and an alcohol or glycol ether-based organic solvent, the anti-glare treatment composition containing 5 to 50 parts by mass of the hydrolysis condensate of the tetraalkoxysilane compound per 100 parts by mass of the total treatment composition, and the organic solvent is one or more mixed solvents, and is present in an amount of 50 to 95 parts by mass per 100 parts by mass of the total treatment composition.
[0009] The coating method of the present invention is as follows: (1) the anti-glare treatment composition of the present invention is spray-coated onto a substrate such as glass so as to achieve a predetermined state; (2) while the heat residue of the sprayed anti-glare treatment layer is in a state of 74 to 95 parts by mass when heated at 180°C for 1 hour, a fluorine-containing antifouling agent is further applied. The basic invention involves spray-coating the treatment agent and then (3) baking it in an oven at 150°C for 30 minutes to form a coating. As a result, a coating film having excellent durability and anti-glare and anti-fouling properties can be formed in a process that shortens the baking process compared to conventional processes and prevents repelling and unevenness in the anti-fouling layer due to contamination of the anti-glare layer. Effect of the Invention
[0010] By using the anti-glare treatment composition and coating method of the present invention, it is possible to form a coating film having excellent durability and anti-glare and anti-fouling properties, using a method that is more environmentally friendly than conventional etching methods, that shortens the baking step compared to conventional spray coating methods which are an alternative to etching methods, and that prevents cissing and unevenness of the anti-fouling layer due to contamination of the anti-glare layer. Specifically, as shown in the following examples, it has been confirmed that the coating surface obtained by the present invention has good haze, gloss, and contact angle with water even after being subjected to abrasion multiple times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will now be described in more detail. In the anti-glare treatment composition of the present invention, the hydrolysis condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst, and the alcohol or glycol ether organic solvent (B) are both essential components for obtaining the anti-glare treatment composition.
[0012] "Hydrolysis and condensation product of tetraalkoxysilane compound in the presence of strong acid catalyst (A)" Tetraalkoxysilane compounds that can be used to produce the hydrolytic condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst include tetraalkoxysilanes such as tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, and tetra-n-butoxysilane, as well as oligomers and polymers produced by hydrolytic condensation of such tetraalkoxysilanes. These may be used alone or in combination of two or more. Among them, tetramethoxysilane oligomer and tetraethoxysilane oligomer are preferably used.
[0013] Commercially available tetraalkoxysilane compounds include methyl orthosilicate (manufactured by Tama Chemicals Co., Ltd.), ethyl orthosilicate (manufactured by Tama Chemicals Co., Ltd.), Wacker Silicate (registered trademark) TES28 (manufactured by Wacker Asahi Kasei Silicones Co., Ltd.), ethyl silicate 28 (manufactured by Colcoat Co., Ltd.), N-propyl silicate (manufactured by Colcoat Co., Ltd.), and N-butyl silicate (manufactured by Colcoat Co., Ltd.). Examples of oligomers of tetramethoxysilane include methyl silicate 51 (manufactured by Colcoat Co., Ltd.), MKC silicate MS51, MKC silicate MS56, MKC silicate MS57, and MKC silicate MS56S (manufactured by Mitsubishi Chemical Corporation). Examples of oligomers of tetraethoxysilane include silicate 40 (manufactured by Tama Chemical Industries Co., Ltd.), ethyl silicate 40, and ethyl silicate 48 (all manufactured by Colcoat Co., Ltd.), Dynasylan (registered trademark) SILBOND (registered trademark) 40 (manufactured by Evonik), and tetraethoxysilane. Examples of polymers of this copolymer include HAS-1, HAS-6, HAS-10, and SS-C1 (all manufactured by Colcoat Co., Ltd.), and examples of other oligomers include EMS-485 (manufactured by Colcoat Co., Ltd.), but are not limited to these.
[0014] The tetraalkoxysilane compound is used in an amount of 1 to 70 parts by mass, preferably 20 to 60 parts by mass, per 100 parts by mass of the hydrolysis condensation product (A) of the tetraalkoxysilane compound in the presence of a strong acid catalyst. If the amount is less than 1 part by mass, the hydrolysis condensation is insufficient, and if the amount exceeds 70 parts by mass, the hydrolysis condensation reaction becomes unstable and a sufficient effect cannot be exhibited.
[0015] "Anti-stain functional agent" In the present invention, a trialkoxysilane compound (C) can be used in combination with the above in order to impart functionality such as stain resistance to the coating film itself depending on the required properties, without decreasing the hardness. Usable trialkoxysilane compounds include methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, 3- Glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-isocyanatopropyltriethoxysilane, trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, 1H,1H,2H,2H -Nonafluorohexyltrimethoxysilane, 1H,1H,2H,2H-Nonafluorohexyltriethoxysilane, 1H,1H,2H,2H-Tridecafluoronormal-octyltrimethoxysilane, 1H,1H,2H,2H-Tridecafluoronormal-octyltriethoxysilane, 1H,1H,2H,2H-Heptadecafluorodecyltrimethoxysilane, 1H,1H,2H,2H-Heptadecafluorodecyltriethoxysilane, [5, 5,6,6,7,7,7-heptafluoro-4,4-bis(trifluoromethyl)heptyl] Trialkoxysilanes such as trimethoxysilane and [5,5,6,6,7,7,7-heptafluoro-4,4-bis(trifluoromethyl)heptyl]triethoxysilane, and tetraalkoxysilanes such as Examples of the silane-based copolymer include, but are not limited to, compounds co-condensed with alkoxysilane. These may be used alone or in combination of two or more.
[0016] "Strong acid catalyst" The strong acid catalyst required for producing the hydrolysis and condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst is an essential component for hydrolysis and condensation of the tetraalkoxysilane compound. In general, in the hydrolysis and condensation of tetraalkoxysilane compounds, in acidic conditions, hydrolysis occurs due to an electrophilic reaction of the alkoxy group with oxygen, followed by dehydration polycondensation between adjacent SiOH groups. Therefore, the chain length tends to be extended linearly due to the influence of steric hindrance. On the other hand, in alkaline conditions, hydrolysis occurs due to a direct nucleophilic reaction with Si, followed by three-dimensional condensation. In the present invention, when the tetraalkoxysilane compound condenses three-dimensionally and forms fine particles in the coating liquid, the particles tend to adhere in powder form during coating, which is thought to have a negative effect on sparkle. Therefore, the hydrolysis and condensation must be carried out in an acidic atmosphere.
[0017] Even when hydrolysis and condensation are carried out using a weak acid, there is a concern that the condensation may proceed three-dimensionally. Therefore, in order to realize the effects of the present invention, it is necessary to use a strongly acidic catalyst and carry out hydrolysis and condensation to extend the chain length in a linear manner.
[0018] As the strong acid catalyst used in the present invention, inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, etc., and organic acids such as p-toluenesulfonic acid, benzenesulfonic acid, 10-camphorsulfonic acid, etc. can be suitably used. Among them, hydrochloric acid and nitric acid are preferred from the viewpoint of not remaining in the coating film after baking treatment.
[0019] In the present invention, the strong acid catalyst is diluted with water to prevent a rapid reaction, and is added in an amount of 0.1 to 10 parts by mass, preferably 0.5 to 5 parts by mass, per 100 parts by mass of the tetraalkoxysilane compound. That is, the strong acid catalyst is used in an amount of 0.001 to 7 parts by mass, preferably 0.1 to 3.0 parts by mass, per 100 parts by mass of the hydrolysis condensate (A) of the tetraalkoxysilane compound in the presence of the strong acid catalyst.
[0020] Water is necessary when preparing the hydrolysis condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst, and is an essential component when hydrolyzing the tetraalkoxysilane compound. In the present invention, water is used in an amount of about 1 to 5 times by mole, and preferably about 2 to 4 times by mole, relative to the alkoxy groups of the tetraalkoxysilane. This is thought to promote the hydrolysis reaction while suppressing the dehydration condensation reaction due to the excess water. In other words, if the amount is less than 1 times by mole relative to the alkoxy groups of the tetraalkoxysilane, hydrolysis becomes insufficient, and if the amount is more than 5 times by mole, the liquid stability becomes poor. decreases. In addition, if the amount of water added is large, the drying property of the coating film decreases and the uneven shape is less likely to occur. Therefore, water is used in an amount of 0.1 to 60 parts by mass, preferably 10 to 40 parts by mass, per 100 parts by mass of the hydrolysis condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst.
[0021] When synthesizing the hydrolysis condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst, an organic solvent is necessary as a solvent. If an alcohol solvent or glycol ether solvent with a long alkyl group is used, there is a concern that a reaction may occur in which the silanol group generated by hydrolysis is converted back into an alkoxy group, so alcohols with a short alkyl group, such as methanol or ethanol, are used.
[0022] For example, methanol (boiling point 65° C.), ethanol (boiling point 78° C.), normal propanol (boiling point 97° C.), isopropyl alcohol (boiling point 82° C.), tertiary butanol (boiling point 82° C.), etc. can be used. The alcohol solvent is used in an amount of 1 to 95 parts by mass, preferably 5 parts by mass, per 100 parts by mass of the hydrolysis and condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst. Use so that the total weight is between 70 and 70 parts by weight. The alcohols used here affect the state of unevenness formation and the coating drying speed when sprayed as an AG treatment agent, so the amount used must be determined by including it in the alcohol or glycol ether organic solvent (B).
[0023] "Alcohols or glycol ether organic solvents (B)" When the hydrolysis condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst is sprayed as an AG treatment agent, it is used after being diluted with an alcohol or glycol ether-based organic solvent (B). The alcohol or glycol ether organic solvent (B) not only serves as a solvent during the hydrolysis and condensation of the tetraalkoxysilane compound, but also plays an important role in forming a coating film having an uneven surface during spray coating. In the present invention, when the component formed by hydrolysis and condensation of tetraalkoxysilane is spray-coated, the solvent dries and the droplets land on a glass substrate or the like, forming a concave-convex shape.
[0024] If the solvent dries quickly, the film formation state is poor and the coating film is formed in a powdery state, whereas if the solvent dries slowly, the film formation state is good, but the uneven shape becomes gentler, sufficient antiglare properties are not exhibited, and the solvent contained in the deposited coating film evaporates during bake hardening, causing the coating film to shrink and crack.
[0025] The blending ratio can be adjusted taking into consideration the spraying conditions. For example, when a glass substrate is used at room temperature, the AG treatment liquid does not dry well immediately after being applied to the glass substrate, so it is necessary to lower the spray discharge amount, coating speed, atomization pressure, etc., but by blending a large amount of a solvent with a low boiling point as the alcohol or glycol ether organic solvent (B), a uniform AG treatment layer can be obtained. Examples of the alcohol or glycol ether organic solvent (B) having a low boiling point include alcohols such as methanol (boiling point 65°C), ethanol (boiling point 78°C), normal propanol (boiling point 97°C), isopropyl alcohol (boiling point 82°C), and tertiary butanol (boiling point 82°C), ketones such as methyl ethyl ketone (boiling point 80°C) and methyl isopropyl ketone (boiling point 93°C), and acetates such as ethyl acetate (boiling point 77°C) and isopropyl acetate (boiling point 89°C), etc. Ethanol and isopropyl alcohol are preferred.
[0026] On the other hand, to shorten the spray time, the glass substrate can be preheated to about 100°C. In this case, since the AG coating applied to the glass substrate dries quickly, an alcohol or glycol ether-based organic solvent (B) with a high boiling point is used. Examples of the alcohol or glycol ether-based organic solvent (B) having a high boiling point include alcohols such as normal butanol (boiling point 118°C), isobutanol (boiling point 108°C), secondary butanol (boiling point 100°C), 1-pentanol (boiling point 138°C), 2-methyl-1-butanol (boiling point 128°C), 3-methyl-1-butanol (boiling point 131°C), 2-pentanol (boiling point 119°C), 1-ethyl-1-propanol (boiling point 116°C), 2-methyl-2-butanol (boiling point 102°C), normal hexanol (boiling point 157°C), ethylene glycol monomethyl ether (boiling point 124°C), ethylene glycol monoethyl ether (boiling point 135°C), ethylene glycol diethyl ether (boiling point 121°C), ethylene glycol monoisopropyl ether (boiling point 141°C), ethylene glycol Examples of the glycol ethers include glycol monobutyl ether (boiling point 171°C), propylene glycol monomethyl ether (boiling point 120°C), propylene glycol monoethyl ether (boiling point 132°C), propylene glycol mononormal propyl ether (boiling point 149°C), and propylene glycol mononormal butyl ether (boiling point 171°C). Ketones include methyl normal propyl ketone (boiling point 103°C) and methyl isobutyl ketone (boiling point 116°C). Acetates include normal propyl acetate (boiling point 102°C), butyl acetate (boiling point 127°C), propylene glycol monomethyl ether acetate (boiling point 147°C), ethylene glycol monomethyl ether acetate (boiling point 145°C), and ethylene glycol monoethyl ether acetate (boiling point 156°C).
[0027] Of these, propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate are preferred. Regarding the selection of the solvent, one or more of these can be used in combination, taking into consideration the stability and drying property of the liquid.
[0028] "Other additives" In the present invention, if necessary, a wetting agent, a thickener, a pigment, a dye, a conductivity imparting agent, a filler such as hollow, chain-like, or porous solid silica particles, metal fine particles, etc. may be added to the antiglare treatment composition within a range that does not adversely affect the properties. Among these, examples of fillers such as hollow or chain-like, porous solid silica particles include Sururia (registered trademark) 1110 (average particle size 50 nm, heating residue 20%, IPA dispersion), Sururia (registered trademark) 4110 (average particle size 60 nm, heating residue 20%, IPA dispersion, manufactured by JGC Catalysts and Chemicals Co., Ltd.), organosilica sol IPA-ST-UP (average particle size 9-15 nm, heating residue 15%, IPA dispersion), and organosilica sol MEK-ST-UP (average particle size 9-15 nm, heating residue 20%, MEK dispersion) (manufactured by Nissan Chemical Industries, Ltd.).
[0029] "Heating residue" The heat residue of the hydrolysis condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst is usually The amount of SiO2 produced is 0.1 to 40 parts by mass, preferably 5 to 30 parts by mass, per 100 parts by mass of the hydrolysis condensate (A). The type of alkoxy group may vary depending on whether the alkoxy group is mono- or oligomeric. This heating residue has no particular effect so long as it is within the blending amount of the above-mentioned tetraalkoxysilane compound hydrolyzed condensate (A) in the presence of a strong acid catalyst, and can be adjusted by adding alcohol or glycol ether-based organic solvent (B) when applying. Therefore, the blending amount of the tetraalkoxysilane compound hydrolyzed condensate (A) in the presence of a strong acid catalyst can be expressed by parts by mass of all materials.
[0030] "Method of manufacturing anti-glare treatment composition" The method for producing the antiglare treatment composition of the present invention will be described below. The method for producing the anti-glare treatment composition mainly comprises producing a hydrolysis condensation product (A) of a tetraalkoxysilane compound in the presence of a strong acid catalyst, diluting the product with an alcohol or glycol ether organic solvent (B), and filtering the product. The hydrolysis and condensation of the tetraalkoxysilane compound is carried out in an organic solvent. However, when an alcohol solvent or a glycol ether solvent with a long alkyl group is used, there is a concern that a reaction may occur in which the silanol group generated by the hydrolysis is converted back into an alkoxy group. Therefore, alcohols with a short alkyl group, such as methanol or ethanol, are used. A tetraalkoxysilane compound is mixed in a solvent, and while stirring, a strong acid catalyst that has been diluted in advance with water and a solvent is added dropwise. At this time, the liquid temperature is adjusted to be between 10 and 60°C in order to suppress the hydrolysis and condensation reaction. After the dropwise addition is completed, the mixture is kept at a constant temperature of 20 to 40°C for a specified period of time to carry out the hydrolysis and condensation reaction. The reaction conditions are adjusted depending on the type of alkoxy group of the tetraalkoxysilane compound, and a hydrolysis condensation product (A) of the tetraalkoxysilane compound is produced in the presence of a strong acid catalyst. The appropriate viscosity of the hydrolysis condensate (A) of the tetraalkoxysilane compound in the presence of a strong acid catalyst is 1 to 5 mPa s, as measured using a TVB15 (manufactured by Toki Sangyo Co., Ltd.) rotor No. L / Adp at a rotation speed of 100 rpm and a liquid temperature of 30°C. Then, dilute with an alcohol or glycol ether-based organic solvent (B) selected according to the spray conditions, and finish by filtering through a 1 μm filter.
[0031] "Method of applying anti-glare treatment composition" The anti-glare treatment composition of the present invention exerts its effect particularly when spray-coated onto an object to be coated. Spin coating and dip coating produce smooth coating films, not uneven ones, and therefore the desired anti-glare properties cannot be achieved. However, the unevenness that affects the anti-glare properties varies depending on the droplets discharged from the spray, so it is important to set the coating conditions, such as the amount of spray, temperature, and humidity. Since the anti-glare treatment composition is spray-coated and then the AF treatment agent is spray-coated, it is necessary to apply the anti-glare treatment composition onto a substrate such as glass in a predetermined state. The heating residue of the antiglare treatment composition when applied to glass varies depending on the spray coating conditions, temperature and humidity, and substrate heating temperature, and increases from the original heating residue. If the time until spray coating of the AF treatment agent is prolonged, the solvent volatilizes and the heating residue increases further. Therefore, the heat residue of the AG treatment layer that was applied to the glass in advance was heated at 180°C for 1 hour. It is necessary to set conditions such that the amount is 74 to 95 parts by mass when calculating the amount by weight. However, when actually laminating the AF treatment agent, heating at 180°C for 1 hour is not necessary.
[0032] By spray-coating the AF treatment agent onto the anti-glare treatment agent layer sprayed under the above conditions, a coating film having excellent durability and anti-glare and anti-fouling properties can be formed. If the heating residue of the AG treatment layer is less than 74 parts by mass, the formation of the uneven shape of the coating film is insufficient, and anti-glare properties cannot be achieved. If the heating residue is more than 95 parts by mass, the AG treatment layer dries too much, which reduces the adhesion to the AF treatment layer applied later, resulting in a coating film with poor abrasion resistance and durability. The uneven shape of the AG treatment layer was measured using a laser microscope LEXT OLS4100. (Olympus Corporation), the result was 0.05 to 0.25, preferably 0. 075~0.15.
[0033] "Anti-fouling treatment agent" There are no particular restrictions on the antifouling (AF) treatment agent used in the present invention, and any commercially available antifouling treatment agent that can be spray-coated can be used. From the standpoint of antifouling performance and adhesion to the AG layer, however, those made of fluorine-containing organic silicon compounds are preferred. The fluorine-containing organosilicon compound used may be one having one or two or more groups selected from the group consisting of a perfluoropolyether group, a perfluoroalkylene group, and a perfluoroalkyl group. Examples of commercially available products are Optool DSX (manufactured by Daikin Corporation) and KY-100 series (manufactured by Shin-Etsu Chemical Co., Ltd.). Examples include NB06-04 (Katsurayama Technology Co., Ltd.), and NB06-04 (Katsurayama Technology Co., Ltd.).
[0034] The AF treatment agent is preferably applied by spray coating, and the same spray equipment as that used for applying the AG treatment agent can be used. When using spin coating to apply the AF treatment agent, it is difficult to spread the AF treatment agent evenly because the AG layer is an uncured film containing a solvent. In addition, in the vacuum deposition, sputtering, and plasma CVD methods, the pressure is reduced in the chamber, so the AG layer dries out too much, reducing the adhesion with the AF layer.
[0035] "Object to be painted" The substrates to which the anti-glare treatment composition of the present invention can be applied include plastics, glass materials such as glass plates and glass cloths, ceramic materials, metal materials, etc. The present invention is particularly effective for glass materials.
[0036] The following is an example of application of the anti-glare treatment composition of the present invention to glass. A degreased and cleaned glass substrate is used at room temperature or after preheating. After spraying the anti-glare treatment composition, the AF treatment agent is sprayed and then baked and cured at 150°C for about 30 minutes. As for the baking conditions, the composition is sufficiently cured at about 150°C, but it is also possible to heat to 300°C or higher to further improve the hardness of the coating film. The present invention will be described in more detail with reference to Production Examples, Examples, and Comparative Examples, but the present invention is not limited thereto. In the Production Examples, Examples, and Comparative Examples, the parts mean parts by mass unless otherwise specified. EXAMPLES
[0037] "Manufacturing example" Manufacturing Example 1 In a 1-liter flask, 35 parts of tetraethoxysilane (40 parts by mass of SiO2) as a tetraalkoxysilane compound and 18 parts of ethanol as an alcohol solvent with a short alkyl group were added. The contents were charged and mixed at room temperature using a disperser. An aqueous solution of 10% nitric acid (4 parts) diluted with 20 parts of water as a strong acid catalyst was added dropwise to the flask, and the stirring was stopped. The mixture was then stored at 30°C for 6 hours to obtain a hydrolysis condensation product (A) of the tetraalkoxysilane compound. Thereafter, while stirring with a disperser, a mixture of 5 parts of isobutyl alcohol, 403 parts of ethanol, and 15 parts of methanol as an alcohol or glycol ether-based organic solvent (B) was added to dilute the mixture, and the mixture was filtered through a 1 μm filter to obtain 500 parts of AG treatment liquid (heating residue: 2.8%).
[0038] Manufacturing Example 2 500 parts of AG treatment liquid (heating residue 2.8%) was obtained in the same manner as in Production Example 1, except that 403 parts of propylene glycol monomethyl ether acetate was used instead of 403 parts of ethanol as a solvent for diluting the hydrolysis condensation product (A) of the tetraalkoxysilane compound.
[0039] "Example" Example 1 The AG treatment solution obtained in Production Example 1 was spray-coated on a 50 mm x 100 mm x 2 mm soda glass plate (room temperature) that had been degreased in advance with an alkaline detergent, using a precision coating machine (manufactured by Apiros Co., Ltd.) so that the coating film was about 0.4 μm thick, forming an AG coating film. On the AG coating film, NB06-04 (AF treatment solution) was sprayed on the same precision coating machine (manufactured by Apiros Co., Ltd.) using the same precision coating machine (manufactured by Apiros Co., Ltd.). After spraying with Katsurayama Technology, it is baked at 150℃ for 30 minutes and then stacked with AGAF. A layer coating was formed.
[0040] Example 2 An AGAF laminated coating film was formed in the same manner as in Example 1, except that the soda glass plate was heated to 100° C. when the antiglare treatment composition was applied.
[0041] Example 3 An AGAF laminated coating film was formed in the same manner as in Example 2, except that the antiglare treatment liquid obtained in Production Example 2 was used instead of the antiglare treatment liquid obtained in Production Example 1.
[0042] Comparative Example 1 The AG treatment solution obtained in Production Example 1 was spray-coated to a 50 mm x 100 mm x 2 mm soda glass plate (room temperature) that had been degreased with an alkaline detergent in advance, using a precision coating machine (manufactured by Apiros Co., Ltd.) so that the coating film was about 0.4 μm thick, and the plate was pre-dried at 120°C for 20 minutes and then baked at 180°C for 30 minutes to form an AG layer. Next, the AF treatment agent NB06-04 (Katsurayama Technology Co., Ltd.) was spray-coated using the same precision coating machine (manufactured by Apiros Co., Ltd.), and then baked at 150°C for 30 minutes to form an AGAF laminated coating film.
[0043] Comparative Example 2 The AG treatment solution obtained in Production Example 2 was spray-coated on a 50 mm x 100 mm x 2 mm soda glass plate that had been degreased with an alkaline detergent in advance, using a precision coating machine (manufactured by Apiros Co., Ltd.) to coat the plate with a coating thickness of approximately 0.4 μm at a substrate heating temperature of 100°C. After preliminary drying at 120°C for 20 minutes, The AG coating was formed by baking at 180°C for 30 minutes. After the AG coating was formed, the AF treatment liquid NB06-04 (Katsurayama Technology Co., Ltd.) was used and sprayed with a precision coating machine (Apiros Co., Ltd.). After coating, it was baked at 150°C for 30 minutes to form an AGAF laminated coating film.
[0044] Comparative Example 3 The AG treatment solution obtained in Production Example 1 was spray-coated on a 50 mm x 100 mm x 2 mm soda glass plate (room temperature) that had been degreased in advance with an alkaline detergent, using a precision coating machine (manufactured by Apiros Co., Ltd.) so that the coating film would be approximately 0.4 μm thick. The plate was pre-dried at 120°C for 20 minutes, and then baked at 180°C for 30 minutes to form an AG coating film. The AG coating film was then coated with an alkaline detergent (Yokohama Resin Industrial Co., Ltd. After washing with AF-1000 (manufactured by AF Chemical Industries, Ltd.), the plate was washed with water three times and dried in a dryer at 50°C for 5 minutes. The treatment liquid NB06-04 (Katsurayama Technology Co., Ltd.) was sprayed using a precision coating machine (Apiros Co., Ltd.) and baked at 150°C for 30 minutes to form an AGAF laminated coating film.
[0045] Comparative Example 4 The AG treatment solution obtained in Production Example 1 was spray-coated on a 50 mm x 100 mm x 2 mm soda glass plate that had been degreased in advance with an alkaline detergent using a precision coating machine (manufactured by Apiros Co., Ltd.) so that the coating thickness was approximately 0.4 μm. The plate was pre-dried at 120°C for 20 minutes and then baked at 180°C for 30 minutes to form an AG coating film. The AG coating film was subjected to plasma treatment for 20 minutes using a plasma generator (manufactured by Yamato Scientific Co., Ltd.). After the plasma treatment, the AF treatment solution NB06-04 (manufactured by Yamato Scientific Co., Ltd.) was added. The coating was done by a precision coating machine (manufactured by Apiros Co., Ltd.) The AGAF laminated coating was formed by baking at 150°C for 30 minutes.
[0046] Comparative Example 5 An AGAF laminated coating film was formed in the same manner as in Example 1, except that the AG treatment liquid obtained in Production Example 2 was used instead of the AG treatment liquid obtained in Production Example 1.
[0047] (evaluation) Examples 1 to 3 and Comparative Examples 1 to 5 were evaluated for the following items. The evaluation results are shown in Table 2.
[0048] (1) Haze The haze was evaluated based on the haze value measured using a haze meter NDH7000 (manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7136:2000. (2) Gloss Using Microgloss 60° (manufactured by BYK), a black piece of cloth was placed on the back of the glass substrate and the gloss of the coating surface was measured and evaluated. (3) Water contact angle The contact angle of water on the coating surface was measured and evaluated using PCA-11 (manufactured by Kyowa Interface Science Co., Ltd.). (4) Abrasion resistance In accordance with JIS L8049:2013, the test pieces were abraded using TL201t (manufactured by Trinity Lab Co., Ltd.), and the coating film was evaluated as follows (1) to (3). (5) Measurement of heat residue after anti-glare treatment The weight (a) of the glass substrate after degreasing is measured, and the weight (b) is measured after applying the AG treatment agent. After that, it is dried at 180°C in a drying oven for 1 hour, and the weight (c) after baking is measured. The heating residue was calculated from the weight using the following formula.
[0049]
number
[0050] The abrasion resistance test conditions for evaluation (4) are shown in Table 1.
[0051] [Table 1]
[0052] [Table 2]
[0053] The target value for AF performance is preferably a water contact angle of 100° or more after 10,000 abrasion cycles. Examples 1 to 3 maintained a high contact angle even after 10,000 abrasion tests. I held it. In Comparative Examples 1 and 2, baking was performed after application of the AG treatment agent, so the heating residue of the AG layer was higher than the standard, and the contact angle after the abrasion test decreased significantly. In Comparative Example 5, a high boiling point solvent was used to dilute the AG treatment agent, and the glass substrate was not heated before application of the AG treatment agent, so the heating residue of the AG layer was lower than the standard, and antiglare properties were not exhibited. In Comparative Examples 3 and 4, the number of steps was increased compared to the other examples because a surface modification process of the AG layer was incorporated, but the contact angle after the abrasion test was equivalent to that of Examples 1 and 3. From the above results, it was confirmed that by spraying the AG treatment agent so that the heating residue is 74% to 95% as in Examples 1 to 3, and then spraying the AF treatment agent in the same manner and then baking it, it is possible to obtain a durable AGAF laminated film while reducing the overall processing time. [Industrial Applicability]
[0054] By using the anti-glare treatment composition and anti-glare and anti-soiling (AGAF) lamination method of the present invention, the treatment time can be shortened and production efficiency can be improved. Furthermore, the obtained laminated coating film has excellent abrasion resistance and durability, making it extremely useful in industry.
Claims
1. An anti-glare treatment composition comprising a hydrolysis condensate of a tetraalkoxysilane compound in the presence of a strong acid catalyst, and an alcohol or glycol ether organic solvent.
2. The anti-glare treatment composition according to claim 1, characterized in that it contains 5 to 50 parts by mass of a hydrolysis condensate of a tetraalkoxysilane compound per 100 parts by mass of the anti-glare treatment composition according to claim 1, and the organic solvent according to claim 1 is one or more mixed solvents and is contained in an amount of 50 to 95 parts by mass per 100 parts by mass of the anti-glare treatment composition according to claim 1.
3. A method for forming a coating film having antiglare and antifouling properties using the antiglare treatment composition according to claim 1, A method for forming a coating film having anti-glare and anti-fouling properties, comprising coating the surface of an article with an anti-glare treatment composition to form an anti-glare treatment layer, subsequently coating the surface with a fluorine-containing anti-fouling treatment agent, and then baking the same.
4. The method for forming a coating film having antiglare and antifouling properties according to claim 3, characterized in that the antifouling treatment agent is spray-coated while the antiglare treatment composition layer is in a state in which the heating residue determined by heating at 180°C for 1 hour is 74 to 95 parts by mass.
5. An antiglare and antifouling layer comprising an antiglare layer comprising the antiglare treatment composition according to claim 1 and an antifouling layer comprising a fluorine-containing antifouling treatment agent.
Citation Information
Patent Citations
Stainproof layer-forming composition and reflection-preventing laminate
JP2006124417A
Antiglare antireflection film and display device
JP2008224718A
Article having transparent base material and antifouling-antireflection film and manufacturing method thereof
JP2015049319A
Antifouling antireflection film, article and production method thereof
JP2016001200A
Water-repellent substrate and process for production thereof
WO2010007956A1